Analisis Istinbath Hukum pada Fatwa DSN-MUI No.147/DSN-MUI/XII/2021 Tentang Penyelenggaraan Jaminan Sosial Ketenagakerjaan Berdasarkan Prinsip Syariah - Irsyadi, Muhammad Lingga; Slamet, Jundi Qoriba (Department of Islamic Economics Law, 2024)
This study aimed to analyze the reason behind of istinbath related to BPJS fatwa. The type of research used by researchers is Normative Islamic Law research using secondary data. Meanwhile, the secondary data used is DSN-MUI Fatwa No. 147 of 2021 concerning implementation Employment social security is based on sharia principles, the nature of this research is descriptive qualitative with data collection through literature study. The result showed that analysis of Legal Istinbatı in the 2021 DSN-MUI Fatwa concerning the Implementation of Employment Social Security based on sharia principles, namely every contract contained in the fatwa This is permissible, on the basis of extracting standard laws owned by the National Sharia Council of the Indonesian Ulema Council, in which the DSN-MUI as a Fatwa institution established in Indonesia implements the concept of Istinbath. The law is Collective Ijtihad based on the Al-Qur'an and Hadith, ijma, Qiyas and other mu''tabar propositions Including other legal Istinbath methods such as Istihsan Istishab,